Social innovation from value creation in high quality coffees in the department of Nariño (2016)
This book describes the history of Nariño coffe growing from the voice of actors and managers involved in the process of appropriating the coffe chain as a value chain in the municipality of La Union (department of Nariño, Colombia). It starts voice and has engaged in dialogue and participatory decision scenarios motivated by the desire to give his production work a new status: entrepreneur. The strengthening processes in as-sociations supported by entities such as Fundacion Social and underpin this work. The book consists of six chapters that deal with the main socio-political and economic aspects of Nariño, and areas for improvement, as well as the background that en-abled the implementation of a roasting plant in La Union. This viable and sustainable job for farmers in Colombia. It is aimed at producers and managers of prioritized production chains in Nariño, research groups, entrepreneurs, departmental and municipal governments, scholars, scientists and students, and the general public interested in knowing in depth how social innovation processes are managed in the department of Nariño.